The Idea of Progress in Forensic Authorship Analysis - Grant, Tim (Social Sciences, 2022)
This Element examines progress in research and practice in forensic authorship analysis. It describes the existing research base and examines what makes an authorship analysis more or less reliable. This title is also available as Open Access on Cambridge Core.